2015
DOI: 10.1144/sp404.16
|View full text |Cite
|
Sign up to set email alerts
|

Strata and time: probing the gaps in our understanding

Abstract: Sedimentary strata are the paramount source of geohistorical information. The 'frozen accidents' of individual deposits preserve evidence of past physical, chemical and biological processes at the Earth's surface, while the spatial relationships between strata (especially superposition) yield successions of events through time. There is, however, no one-to-one relationship between strata and time, and the interpretation of the stratigraphic record depends on an understanding of its limitations. Stratigraphic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…More recently, Kemp and Sadler () demonstrated that the number and duration of intervals of nondeposition or erosion increases over time. In stratigraphy it is also now recognized that the duration of the gaps, the distribution of layer thicknesses and the sedimentation rate have fractal properties ( Bailey & Smith, ; Plotnick, ; Sadler, ; Schlager, ; D. G. Smith et al, ). Furthermore, a recent Martian model proposed by Horvath and Andrews‐Hanna () predicts the presence of numerous small lakes around Gale crater even if there are no sediments preserved within them or other geological evidence that supports past groundwater upwelling events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Kemp and Sadler () demonstrated that the number and duration of intervals of nondeposition or erosion increases over time. In stratigraphy it is also now recognized that the duration of the gaps, the distribution of layer thicknesses and the sedimentation rate have fractal properties ( Bailey & Smith, ; Plotnick, ; Sadler, ; Schlager, ; D. G. Smith et al, ). Furthermore, a recent Martian model proposed by Horvath and Andrews‐Hanna () predicts the presence of numerous small lakes around Gale crater even if there are no sediments preserved within them or other geological evidence that supports past groundwater upwelling events.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kemp and Sadler (2014) demonstrated that the number and duration of intervals of nondeposition or erosion increases over time. In stratigraphy it is also now recognized that the duration of the gaps, the distribution of layer thicknesses and the sedimentation rate have fractal properties ( Bailey & Smith, 2005;Plotnick, 1986;Sadler, 1999;Schlager, 2004;D. G. Smith et al, 2015).…”
Section: Lack Of Sediment Inside Deep Basinsmentioning
confidence: 99%
“…GSSPs represent the benchmarks for definition of all of the principal boundaries of the geological time-scale (e.g. Smith et al 2014). Each GSSP is a specific stratigraphical horizon in a particular section that has been chosen to formally define the basal boundary of any chronostratigraphical unit at the stage level or higher.…”
mentioning
confidence: 99%
“…Davies et al 2011;Melchin et al 2012) and are in need of restudy. The base of the Silurian System has been formally redefined in terms of its biostratigraphical definition (Rong et al 2008), and several of the other Silurian GSSPs are currently under restudy (Smith et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation